The Effectiveness of Government Policies on the Prevention of Early Marriage in South Bolaang Mongondow Regency - Ismail, Fendawati; B, Sumiyati; Djafar, Marwan (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to analyze the effectiveness of the South Bolaang Mongondow Regency Government's policies on the prevention of early marriage. The problem of child marriage is still a crucial issue in Indonesia because it has an impact on the quality of human resources, education, and the health of the younger generation. South Bolaang Mongondow Regency (Bolsel) has demographic characteristics that show that around 24.4% of the population is 0–14 years old out of a total of 75,374 people, so it has a high potential risk to the practice of early marriage. This study uses a descriptive qualitative approach with two problem formulations, namely: (1) how to form and implement government policies in preventing early marriage, and (2) how effective these policies are in reducing the practice of child marriage in the community. The results of the study show that the local government through the Office of Population Control, Family Planning, Women's Empowerment and Child Protection (PPKBP3A) has implemented socialization, education, and cross-sector collaboration programs in an effort to prevent early marriage, such as counseling activities in Pintadia Village, Bolaang Uki District in June 2025. This policy shows a positive direction because it increases public awareness about the dangers of child marriage, but its effectiveness is not optimal. Factors that hinder include lack of coordination between agencies, budget limitations, lack of integrated data, and strong family cultural and economic influence.